2015
DOI: 10.12669/pjms.312.6653
|View full text |Cite
|
Sign up to set email alerts
|

Impact of polymorphisms of the DNA repair gene XRCC1 and their role in the risk of prostate cancer

Abstract: Objective:We conducted a case-control study to examine the role of XRCC1 codons 194 (Arg>Trp), 280 (Arg>His) and 399 (Arg>Gln) polymorphisms in the risk of prostate cancer.Methods:This study included 572 consecutive primary prostate cancer patients and 572 controls between January 2011 and January 2014. The polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) was performed to detect XRCC1 codons 194 (Arg>Trp), 280 (Arg>His) and 399 (Arg>Gln) polymorphisms.Results:Compared with the cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…Table 1 showed the characteristics of all the eligible studies and genotype frequency distributions of twelve polymorphisms in five XRCC genes ( XRCC1 -rs915927, XRCC1 -rs25489, XRCC1 -rs25487, XRCC1 -rs1799782, XRCC1 -rs3213245, XRCC2 -rs3218536, XRCC3 -rs1799796, XRCC3 -rs861539, XRCC4 -rs6869366, XRCC4 -rs28360071, XRCC4 -rs1805377, XRCC7 -rs7003908) included in current meta-analysis (Agalliu et al, 2010, Andrew et al, 2015, Andrew et al, 2007, Andrew et al, 2006, Arizono et al, 2008, Berhane et al, 2012, Broberg et al, 2005, Chang et al, 2009, Lan et al, 2006, Lavender et al, 2010, Chang et al, 2008, Dhillon et al, 2009, Figueroa et al, 2007a, Figueroa et al, 2007b, Fontana et al, 2008, Gangwar et al, 2009, Hamano et al, 2008, Hirata et al, 2006, Hirata et al, 2007, Huang et al, 2007, Abe et al, 2011, Mittal et al, 2008, Narter et al, 2009, Nowacka-Zawisza et al, 2015, Ramaniuk et al, 2014, Ritchey et al, 2005, Rybicki et al, 2004, Sak et al, 2007, Sanyal et al, 2004, Shen et al, 2003, Stern et al, 2002, Stern et al, 2001, Van Gils et al, 2002, Wang et al, 2010, Wang et al, 2008, Wen et al, 2009, Wen et al, 2013, Wu et al, 2006, Xu et al, 2007, Zhi et al, 2012, Hao et al, 2008, Zhou et al, 2012, Zhu et al, 2014, Zhu et al, 2012, Kelsey et al, 2004, Kuasne et al, 2011, Luedeke et al, 2009, Mandal et al, 2010, Mandal et al, 2011, Matullo, 2005, Matullo et al, 2006, Matullo et al, 2001, Mittal et al, 2012a, Mittal et al, 2012b). The study selection processes were presented in Supplementary Figs.…”
Section: Resultsmentioning
confidence: 99%
“…Table 1 showed the characteristics of all the eligible studies and genotype frequency distributions of twelve polymorphisms in five XRCC genes ( XRCC1 -rs915927, XRCC1 -rs25489, XRCC1 -rs25487, XRCC1 -rs1799782, XRCC1 -rs3213245, XRCC2 -rs3218536, XRCC3 -rs1799796, XRCC3 -rs861539, XRCC4 -rs6869366, XRCC4 -rs28360071, XRCC4 -rs1805377, XRCC7 -rs7003908) included in current meta-analysis (Agalliu et al, 2010, Andrew et al, 2015, Andrew et al, 2007, Andrew et al, 2006, Arizono et al, 2008, Berhane et al, 2012, Broberg et al, 2005, Chang et al, 2009, Lan et al, 2006, Lavender et al, 2010, Chang et al, 2008, Dhillon et al, 2009, Figueroa et al, 2007a, Figueroa et al, 2007b, Fontana et al, 2008, Gangwar et al, 2009, Hamano et al, 2008, Hirata et al, 2006, Hirata et al, 2007, Huang et al, 2007, Abe et al, 2011, Mittal et al, 2008, Narter et al, 2009, Nowacka-Zawisza et al, 2015, Ramaniuk et al, 2014, Ritchey et al, 2005, Rybicki et al, 2004, Sak et al, 2007, Sanyal et al, 2004, Shen et al, 2003, Stern et al, 2002, Stern et al, 2001, Van Gils et al, 2002, Wang et al, 2010, Wang et al, 2008, Wen et al, 2009, Wen et al, 2013, Wu et al, 2006, Xu et al, 2007, Zhi et al, 2012, Hao et al, 2008, Zhou et al, 2012, Zhu et al, 2014, Zhu et al, 2012, Kelsey et al, 2004, Kuasne et al, 2011, Luedeke et al, 2009, Mandal et al, 2010, Mandal et al, 2011, Matullo, 2005, Matullo et al, 2006, Matullo et al, 2001, Mittal et al, 2012a, Mittal et al, 2012b). The study selection processes were presented in Supplementary Figs.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, Guo et al (2015) established that this same variant might be correlated with increased risk of breast cancer using a meta-analysis of 13 published case-control studies. However, Hsu et al (2015) found no significant association between XRCC1 gene polymorphisms and skin cancer risk, although in a case-control study, Zhu et al (2015) demonstrated that individuals carrying the Arg194Trp variation in this gene are more susceptible to prostate cancer. Several investigators have scrutinized the association between XRCC1 gene polymorphisms and gastric cancer risk, but their results have been inconsistent (Yan et al, 2009;Engin et al, 2011;Yuan et al, 2011;Karahalil et al, 2012;Pan et al, 2012;Wen et al, 2012).…”
Section: Discussionmentioning
confidence: 97%
“…Previous studies have reported associations between XRCC1 sequence variations and development of several cancers, including those of the lung, colorectum, ovary, breast, skin, and prostate (Guo et al, 2015;Han et al, 2015;Hsu et al, 2015;Malisic et al, 2015;Nissar et al, 2015;Zhu et al, 2015). For example, Han et al (2015) conducted a case-control study, reporting that the Arg399Gln polymorphism significantly elevates susceptibility to non-small cell lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have assessed the role of the XRCC1 Arg399Gln, Arg280His, and Arg194Trp polymorphisms in the development of several types of cancers, such as non-small cell lung cancer (NSCLC), prostate cancer, glioma, breast cancer, ovarian cancer, and colorectal cancer (Kang et al, 2015;Han et al, 2015;Zhu et al, 2015;Wang et al, 2015;Guo et al, 2015;Malisic et al, 2015;Nissar et al, 2015). For example, Kang et al (2015) conducted a study on 210 NSCLC patients and 210 health control subjects in China to investigate the role of the XRCC1 Arg399Gln, Arg280His, and Arg194Trp polymorphisms in the risk of NSCLC.…”
Section: Discussionmentioning
confidence: 99%
“…They found that the XRCC1 Arg194Trp polymorphism increased the risk of NSCLC development. Zhu et al (2015) examined the role of the XRCC1 Arg399Gln, Arg280His, and Arg194Trp polymorphisms in the risk of prostate cancer, and showed an increased risk for prostate cancer in individuals with the XRCC1 Arg194Trp polymorphism. Wang et al (2015) conducted a study on 387 glioma patients and 400 cancer-free controls, and found that the XRCC1 Arg399Gln polymorphism was associated with glioma susceptibility.…”
Section: Discussionmentioning
confidence: 99%